Exploration of Ethno-medicinal Knowledge among Periurban Community of Hurip Jaya Village, Babelan, District Bekasi, West Java - Nonon Saribanon; Kamelia Putri Utami; Sri Endarti Rahayu (Journal of Tropical Biodiversity, 2021)
The role of the community in the use of medicinal plants is very important to encourage the development of natural resources in the surrounding environment and improve the degree of public health. Medicinal plants that have been widely researched and are often used by the people of Indonesia since a long time ago, can be an alternative treatment or support conventional treatment therapies. The purpose of this study was to determine changes in society in relation to the use of medicinal plants, document the diversity of medicinal plants and how to use medicinal plants by the community, and obtain a list of plant species based on the use value of disease categories. Data collection is done by open interviews, participatory observation, focus group discussions (FGD). Data were analyzed descriptively to describe the changes that occurred in the community before and after the existence of medicinal plants, inventorying the composition of medicinal plant species and how to use them. Quantitative analysis is done by calculating the Local User's Value Index (LUVI). The changes that occur are people using medicinal plants for cultivation, curing diseases and maintaining health. There are 44 plant species from 40 genera and 26 plant tribes used to cure 46 diseases. Asteraceae is a plant species with the highest number of species that are used as medicinal ingredients. Based on the calculation of the value of LUVI, Dayak onions are medicinal plants that have the highest score, which is 6%. Then followed by bay leaves 4.65% and sidaguri 4.55%. Ten common diseases that occur in the community are diarrhea, gout, cholesterol, high blood pressure, gastritis, rheumatism, asthma migraine, stroke, fever. Utilization of medicinal plants carried out by the community that is, by making processed products such as instant simplicia powder, dried simplicia, herbal medicine and tea bags. There is a change in the use of medicinal plants from previously not using medicinal plants and currently using medicinal plants to cure a disease and maintain health. The change occurred because of the existence of the non-governmental organization Aliksa as a facilitator and local leader who managed and assisted the cultivation and utilization program of medicinal plants. Common diseases that occur in the people of Hurip Jaya village are diarrhea, gout, cholesterol, high blood pressure, gastritis, rheumatism, asthma migraine, stroke, fever. Utilization of medicinal plants used as processed products such as instant simplicia powder, dried simplicia, herbal medicine and tea bags.